2005
DOI: 10.2337/diabetes.54.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Dissipating Excess Energy Stored in the Liver Is a Potential Treatment Strategy for Diabetes Associated With Obesity

Abstract: For examining whether dissipating excess energy in the liver is a possible therapeutic approach to high-fat diet-induced metabolic disorders, uncoupling protein-1 (UCP1) was expressed in murine liver using adenoviral vectors in mice with high-fat diet-induced diabetes and obesity, and in standard diet-fed lean mice. Once diabetes with obesity developed, hepatic UCP1 expression increased energy expenditure, decreased body weight, and reduced fat in the liver and adipose tissues, resulting in markedly improved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 42 publications
6
56
1
Order By: Relevance
“…15 Hepatic mitochondrial adaptations are particularly interesting since dissipating energy stored in the liver has been suggested as a potential treatment strategy for diabetes associated with obesity. 46 Even though, in the present study, we cannot conclude that the enhanced free radical generation by liver mitochondria of Lou/C rats ( Figure 1) was entirely responsible for mitochondrial adaptations, a recent study suggested that oxidative stress provided by treatment with H 2 O 2 induced depolymerization of microtubules and this event is one of the molecular events involved in the increase in mitochondrial mass upon treatment of human cells with H 2 O 2 . 47 On the basis of a greater capacity for reoxidizing FADH 2 evidenced with G/M/S and octanoylcarnitine, we propose that the enhanced liver mitochondrial H 2 O 2 production in Lou/C rats was due to increases in reverse electron flow through the respiratory-chain complex I and to higher medium-chain acyl-CoA dehydrogenase activity.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…15 Hepatic mitochondrial adaptations are particularly interesting since dissipating energy stored in the liver has been suggested as a potential treatment strategy for diabetes associated with obesity. 46 Even though, in the present study, we cannot conclude that the enhanced free radical generation by liver mitochondria of Lou/C rats ( Figure 1) was entirely responsible for mitochondrial adaptations, a recent study suggested that oxidative stress provided by treatment with H 2 O 2 induced depolymerization of microtubules and this event is one of the molecular events involved in the increase in mitochondrial mass upon treatment of human cells with H 2 O 2 . 47 On the basis of a greater capacity for reoxidizing FADH 2 evidenced with G/M/S and octanoylcarnitine, we propose that the enhanced liver mitochondrial H 2 O 2 production in Lou/C rats was due to increases in reverse electron flow through the respiratory-chain complex I and to higher medium-chain acyl-CoA dehydrogenase activity.…”
Section: Discussioncontrasting
confidence: 68%
“…These hepatic mitochondrial characteristics may be of particular interest if we take into account that (1) liver fat accumulation is one of the detrimental events involved in the development of insulin resistance and type 2 diabetes 13 and (2) dissipating excess energy in the liver (mitochondrial uncoupling) is a possible therapeutic approach to high-fat diet-induced metabolic disorders. 46 Such liver adaptations could probably explain the higher insulin sensitivity displayed by Lou/C rats (Couturier K, unpublished data) and the ability of this strain to resist fat accretion and insulin resistance with aging 4 or high-fat diet 2,15 in spite of a strong preference for fat. 5,8,15 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of ectopic UCP1 resulted in reduced expression of genes characteristic of differentiated energy-storing adipocytes, such as peroxisome proliferator-activated receptor gamma (PPARc) and aP2 , in analogy with the induction of ''fat burning adipocytes'' in response to leptin treatment in rats (Zhou et al 1999). In accordance, mitochondrial uncoupling in adipocytes in vitro led to lower intracellular ATP concentrations (Yamada et al 2006;Si et al 2009), up-regulation of glycolysis and mitochondrial biogenesis, and down-regulation of energyconsuming pathways such as fatty acid synthesis (Rossmeisl et al 2000;Si et al 2009;Senocak et al 2007), while lactate production was increased (Rossmeisl et al 2000; ) N D Decreased (Ishigaki et al 2005) Mitochondrial biogenesis and/or content Increased (Rossmeisl et al 2002) Content decreased (Han et al 2004) N D Mitochondrial ROS production ND Reduced (Keipert et al 2010) N D Cellular ATP levels Decreased Yamada et al 2006); increased AMP/ATP ratio Unchanged (Li et al 2000) or decreased (Li et al 2000;Couplan et al 2002;Han et al 2004 Rossmeisl et al, unpublished) suggested an upregulation of lipid catabolism in SM of high-fat diet-fed mice in response to the transgenic UCP1 expression in WAT, which is also associated with hypolipidemic effects, especially under fasted conditions. The effect of UCP1 expression on SM phenotype was studied in detail by Couplan et al (2002), who reported a fiber type switch from fast glycolytic fibers to slow oxidative fibers in gastrocnemius and plantaris muscle accompanied by a reduced muscle mass.…”
Section: Metabolic Effects Of Ectopic Ucp1 At Cellular and Tissue Levelsmentioning
confidence: 93%
“…Liver Ishigaki et al (2005), using an adenoviral vector, induced a transient UCP1 gene expression in the liver of mice rendered obese and insulin resistant by prior feeding of a highfat diet. UCP1 content in liver mitochondria peaked at 3-7 days after the adenovirus injection, followed by a decline in the expression.…”
Section: Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation